1996
DOI: 10.1029/96jd01618
|View full text |Cite
|
Sign up to set email alerts
|

On the retrieval of lightning radio sources from time‐of‐arrival data

Abstract: We examine the problem of retrieving three‐dimensional lightning locations from radio frequency time‐of‐arrival (TOA) measurements. Arbitrary antenna locations are considered. By judiciously differencing measurements that are related to the location of the antennas and their excitation times, the problem is converted from the initial spherical nonlinear form to a system of linear equations. In the linear formalism, the source location and time‐of‐occurrence is viewed geometrically as an intersection of hyperpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 10 publications
0
26
0
Order By: Relevance
“…Most of the early TOA work has been conducted following this method and solving non‐linear equations numerically to get the retrieval locations. However Koshak and Solakiewicz [] introduced a method to linearize these non‐linear equations and introduced analytical solutions to get the location as well as the errors for each coordinate. In the perfect situation, five stations produce four linear equations, and getting analytical solutions to four unknowns ( x , y , z , t ) would be trivial.…”
Section: Methods and Calculationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the early TOA work has been conducted following this method and solving non‐linear equations numerically to get the retrieval locations. However Koshak and Solakiewicz [] introduced a method to linearize these non‐linear equations and introduced analytical solutions to get the location as well as the errors for each coordinate. In the perfect situation, five stations produce four linear equations, and getting analytical solutions to four unknowns ( x , y , z , t ) would be trivial.…”
Section: Methods and Calculationsmentioning
confidence: 99%
“…In the perfect situation, five stations produce four linear equations, and getting analytical solutions to four unknowns ( x , y , z , t ) would be trivial. These authors also indicated that this linear system “can be taken as an under‐ or over‐determined system of equations that can be solved using the general theory of constrained linear inversion.” Koshak and Solakiewicz [] applied this method for theoretical sensor configurations: a square network having a sensor at each corner, a triangular network having a sensor at each corner plus a fourth sensor at the center, and a symmetric seven‐antenna network having sensors at each corner of a hexagon and one at the center. They determined that the mean location errors were smallest for the symmetric seven‐antenna network.…”
Section: Methods and Calculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the measurement characteristics of the system (direction finders, GPS time stamps, etc.) another differentiation is in the number of dimensions (e.g., resolving the 3D structure of a lightning stroke versus just its spatial location) involved in the location retrieval, which varies according to the operation frequency bandwidth [ Koshak and Solakiewicz , 1996].…”
Section: Introductionmentioning
confidence: 99%
“…The problem of detection of locations of lightning events on the basis of ground-based measurements has been studied extensively within the last three decades [see, e.g., Cianos et al, 1972;Hager and Wang, 1995;Koshak and Solakiewicz, 1996;Lee, 1986;Lewis et al, 1960;MacClement andMurty, 1978;Murty and MacClement, 1973;Panyukov and Strauss, 1996;Proctor, 1971; Rustan et al, 1980;Taylor, 1978;Thompson et al, 1994]. All of the authors derive the location of a lightning event from the times of arrival of electromagnetic radiation at several locations.…”
Section: Introductionmentioning
confidence: 99%